Ion-pair compounds of diacerein for enhancing skin permeability in vitro: the compatibility-permeability relationship of counter ion and diacerein - Yan Liang; Manzhen Duan; Wei Yi; Teng Zhang; Yonggang Wang; Zhiming Wu; Huaibo Tang (Taylor & Francis Group, 2022)
This research aimed to investigate how the relationship between counter ion and diacerein (DCN) exerts an effect on the skin penetration of DCN ion-pair compounds. After the ion-pair compounds were formed by DCN and organic amines with different functional groups, the hydrogen bond of these compounds was confirmed by Fourier-transform infrared (FTIR) spectroscopy and molecular docking. The skin of porcine ears was employed to conduct the in vitro skin penetration, DCN - triethanolamine was the most potential candidate with the Q24h of 7.89 ± 0.38 µg/cm2 among organic amines with different functional groups. Whereas among the homologous fatty amine, the most permeable compound was DCN - lauryl amine with the Q24h of 11.28 ± 0.48 µg/cm2. Molecular simulation was employed to explore the relationship between counter ion and DCN. It was revealed by the bind energy curve that DCN had the strongest compatibility with triethanolamine among organic amines and laurylamine (N12) among fatty amines. It was amazingly found that the in vitro permeation fluxes of DCN ion-pair compounds would increase with enhancing the compatibility of counter ion and DCN. These findings broadened our understanding of how the relationship between drug and counter ion affects the skin penetration of ion-pair compounds.